ON THE POSSIBILITY OF CREATION OF THE ARMENIAN SCHOOL OF TRANSCENDENTAL PSYCHOLOGY - Naghdyan , R. M. (Modern Psychology, 2020)
The article emphasizes the difference between the methodological approach of A.I. Mirakyan to the study of psychic phenomena from the methodologies that dominate in modern psychology. In this context, the possibility of creating of the "own" school of transcendental psychology in Armenia is shown.
Keywords: psyche; methodology; transcendental psychology; psychological school